(untitled) (Research, Society and Development, 2020)
Introduction: Duchenne Muscular Dystrophy (DMD) is characterized by membrane dissociation, resulting in the breakdown of the musculoskeletal fiber. Objective: to identify the assessment tools used to measure the quality of life in patients with DMD. Methodology: A systematic review of articles published from 2007 to 2017 on QOL assessment tools in patients with DMD was conducted in the SciELO, PubMED and LILACS databases. Results: 6 articles met the inclusion criteria, using the QOL assessment tools; Life Satisfaction Index for Adolescents; Quality of Life Evaluation Scale; Medical Outcomes Study 36; World Health Organization Quality of Life Instrument; Health Related Quality of Life Questionnaire for Children and Young People and their Parents e Pediatric Quality of Life Inventory. Conclusions: the tools for the evaluation of quality of life in patients with Duchenne Muscular Dystrophy (DMD) are essentials to determinate and to present an effective treatment focused on patient’s priorities and their main difficulties. However the lack of a validated scale specifically focused on this diagnostic interferes in the real score of those patients quality of life.